1, 1‐Hydroboration and a Borane Adduct of Diphenyldiazomethane: A Potential Prelude to FLP‐N2 Chemistry. Issue 52 (5th December 2017) - Tang, Connie; Liang, Quiming; Jupp, Andrew R.; Johnstone, Timothy C.; Neu, Rebecca C.; Song, Datong; Grimme, Stefan; Stephan, Douglas W.
Abstract: Diphenyldiazomethane reacts with HB(C6 F5 )2 and B(C6 F5 )3, resulting in 1, 1‐hydroboration and adduct formation, respectively. The hydroboration proceeds via a concerted reaction involving initial formation of the Lewis adduct Ph2 CN2 BH(C6 F5 )2 . The highly sensitive adduct Ph2 CN2 (B(C6 F5 )3 ) liberates N2 and generates Ph2 CB(C6 F5 )3 . DFT computations reveal that formation of Ph2 CN2 B(C6 F5 )3 from carbene, N2, and borane is thermodynamically favourable, suggesting steric frustration could preclude carbene–borane adduct formation and affect FLP‐N2 capture. Abstract : N2 the breach… Diphenyldiazomethane reacts with HB(C6 F5 )2 and B(C6 F5 )3 to afford 1, 1‐hydroboration and adduct formation, respectively. The adduct Ph2 CN2 B(C6 F5 )3 liberates N2 and the diphenylcarbene–borane adduct. Computational studies suggest that N2 capture is thermodynamically favourable, despite the exothermicity of carbene–borane adduct formation.